Empowering Privacy: Boosting Public Awareness of Personal Data Protection in the Digital Age - Natamiharja, Rudi; Fakih, M.; Setiawan, Ikhsan; Sujadmiko, Bayu (Probono and Community Service Journal, 2024)
This service aims to enhance awareness of personal data protection among Lampung residents in the digital era. As information technology advances, personal data has become a valuable yet vulnerable asset, at risk of theft, misuse, and privacy violations. Many individuals remain unaware of the importance of safeguarding their data and their rights. Through counseling, training, and outreach in schools, communities, and local institutions, this initiative educates the public on data protection regulations and best practices for securing personal information online. Using a participatory approach, the program engages participants in discussions, simulations, and case studies to foster deeper understanding. Results demonstrate increased knowledge, heightened awareness of data threats, and the adoption of safer digital practices. This initiative aims to empower Lampung's residents to better protect their personal data and mitigate privacy risks in an increasingly digital world.